Single-shot Spinal Versus Epidural Analgesia During Early Labor: A Prospective Randomized Trial - Mohamed, Hadbi; Hasna, Delala; Mohamed, Matouk (British Journal of Healthcare and Medical Research, 2026)
Background: Effective pain relief during labor is essential for maternal comfort and favorable obstetric outcomes. Epidural analgesia (EA) is considered the gold standard ; however, single-shot spinal analgesia (SA) using low-dose local anesthetic represents a faster and simpler alternative, particularly in low-resource settings. Evidence for its use in early labor remains limited. Objective: To compare the efficacy, onset, duration, safety, and maternal-neonatal outcomes of single-shot spinal analgesia versus epidural analgesia initiated at 4 cm cervical dilatation. Methods: In this prospective, randomized, open-label, single-center study, 100 ASA I–II parturients in active labor (4 cm cervical dilatation) were allocated into two groups (n = 50 each). The SA group received an intrathecal injection of 5 mg isobaric bupivacaine combined with 5 μg sufentanil. The EA group received epidural administration of 20 mg bupivacaine with 5 μg sufentanil via catheter. Pain was assessed using the visual analog scale (VAS) at regular intervals. Onset and duration of analgesia, sensory level, motor block, labor duration, need for reinjection, maternal satisfaction, adverse events, oxytocin use, mode of delivery, and neonatal Apgar scores were recorded. Results: Spinal analgesia provided a significantly faster onset of pain relief (1.84 ± 1.09 vs. 8.25 ± 1.88 min, p < 0.001) and quicker achievement of maximal sensory block. Labor duration was significantly shorter in SA for both primiparous and multiparous women (84.06 ± 12.11 vs. 94.78 ± 14.06 min, p < 0.0001). Analgesic efficacy (VAS scores) and maternal satisfaction were comparable between the two groups (96% vs. 90%, p = 0.42). Reinjection was required only in the EA group (16%, p = 0.01). Adverse maternal and neonatal outcomes, were similar between groups. Conclusion: Single-shot spinal analgesia using low-dose bupivacaine provides rapid, effective, and sustained labor analgesia with a safety profile comparable to epidural analgesia. It may represent a valuable, practical alternative in busy obstetric units or resource-limited settings.